Comparative Analysis of Lexical Bundles in Academic Writings by Native English Speakers and Turkish EFL Learners - Aybek Sibel; Can Cem (Darnioji daugiakalbystė)
Authentic language use frequently consists of repeated expressions called multiword units or formulaic utterances (Byrd & Coxhead, 2010), which serve as essential “building blocks of discourse in both spoken and written registers” (Biber & Barbieri, 2007, p. 263). Lexical bundles, a subset of formulaic sequences, are defined as “recurrent expressions, regardless of their idiomaticity, and regardless of their structural status” (Biber et al., 1999, p. 990). This study investigates the use of the most frequent 3- and 4-word lexical bundles in the TICLE, the Turkish component of the International Corpus of Learner English (ICLE), and the Louvain Corpus of Native English Essays (LOCNESS) as the control parallel corpus. The lexical bundles are classified according to their structural and functional characteristics based on the taxonomy developed by Biber et al. (2003; 2004). An interpretative contrastive analysis was conducted between the native (LOCNESS) and non-native (TICLE) data sets. The findings reveal that Turkish EFL learners overuse verb phrase fragments while underusing noun phrase and prepositional phrase fragments. Furthermore, texts in TICLE exhibit a lower lexical variety compared to those in LOCNESS. Regarding functional classification, although Turkish EFL learners produce fewer functional bundles overall, they tend to overuse a limited subset of them. These results suggest underlying issues in EFL pedagogy, particularly the need for explicit instruction on multiword units.